Recursos para o combate à tuberculose em Londrina, PR, Brasil Resources to face tuberculosis in Londrina, State of Paraná, Brazil - Lilia Bueno de Magalhães; Nilton Tornero (Universidade de São Paulo, 1978)
Por meio de informações obtidas em 1976, em visitas ao Dispensário de Tuberculose e ao Sanatório Noel Nutels, órgãos de combate à tuberculose no município de Londrina, PR, Brasil, foi discutida a atuação desses órgãos dentro de um sistema escalonado de prestação de serviços. Foram comentadas várias atividades desses órgãos em relação às recomendações da Divisão Nacional de Tuberculose. A incidência da tuberculose no município de Londrina foi calculada para anos recentes; foi caracterizada a procedência dos casos novos diagnosticados em 1975-76. Critica-se particularmente o uso em massa da abreugrafia, dando-se ênfase à baciloscopia para o diagnóstico e controle dos doentes. At the end of 1976 the authors visited the Tuberculosis Dispensary and the Noel Nutels Sanatory, which are agencies against Tuberculosis in Londrina, State of Paraná, Brazil. Through the obtained information, they discuss the action of these agencies in an echeloned system of referral services; the former for the 17th Sanitary District, having its premises in Londrina, and the latter for the whole of the the North of Paraná, in which it is the only existing Sanatory. Many routines of these agencies are discussed, compared with the recommendations of the National Division of Tuberculosis. The incidence of the disease in Londrina is calculated for the last few years; they characterize the origin of the new cases diagnosed in 1975-76; some other information is presented and commented. Criticism is particularly directed ct the use of mass roentgenphotography, giving emphasis to baciloscopy for the diagnosis and control of the disease.